Urgensi Pendidikan Ekologi melalui Muatan Lokal untuk Mendukung Tercapainya Penetapan Status Kawasan Ekosistem Esensial (KEE) Mangrove Ujungpangkah - Syaiful Huda; Farikhah Farikhah; Prativi Khilyatul Auliya; Churun Lu'lu'il Maknun; Noviatul Rochmah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
University of Muhammadiyah Gresik (UMG) was one of the colleges established in east Java province as the responsible manager of the essential ecosystem area (KEE) mangrove Ujungpangkah. This activity is intended to socialize the importance of ecological education in supporting the success of the deployment of KEE mangrove ujungpangkah status. This study method was a survey conducted by the questionnaire spread to 40 local teachers from elementary school to high school. The questionnaires are collected through the google form. The responders' answers are analyzed descriptively based on their centrality and diversity analysis. The solution in an essay is based on its essence, based on the impelling of ecological education at KEE mengrokah. Based on the results, 100% of respondents consider it is essential to promote ecological education in the Gresik area. 25% do not know about KEE, and 75% have found out about KEE. Based on the data obtained, it is concluded that ecological education needs to be performed and socialized to the community so that the participation from the community is also increasing.